Sustainable negotiation : what physics can teach us about international negotiation - Karsaklian, Eliane, 1959- (Emerald Publishing Limited, 2017)
This new and innovative book introduces a new approach to negotiation, where 'Sustainable Negotiation' replaces the old notion of winning. Instead of 'doing a deal' and walking away, negotiation becomes a continuous process of solving problems and creating relationships with no term limits, which better reflects the real world today. Just as we strive to create a sustainable approach to the natural world, we need to do the same with people if we want to keep working together and building a more harmonious business world. The book borrows from the field of physics to make the case that negotiators need to know what is not visible so they can explain what is visible. This alignment gives negotiators the tools to think differently about what they see, helping them to look beyond traditional negotiation techniques and to develop a forward-thinking and sustainable approach to business. Written by a leading international negotiation expert, Sustainable Negotiation introduces a completely new perspective on international negotiation, providing practical, field-tested examples, experiments and guidance to enable readers to implement sustainable negotiation in the real world.
Includes index.
Keywords: Summit meetings.; Physics.; Business & Economics -- International -- General.; Business strategy.; elektronické knihy; electronic books